Page 440
Chippewa bands, Cree, and other nations who make up the membership of the Turtle Mountain Band. The name Chippewa, a mispronunciation of Ojibwa, Ojibway, Ojibwe, Saulteaux, and Anishinabe, are all nations that refer to the same group of people. The term "Chippewa" is used after European contact. The Ojibway are members of the Algonquin language group, which are located from Newfoundland to the Rocky Mountains and from Hudson Bay to North Carolina. Other tribes in this language group are the Cree, Ottawa, Sauk Fox, Menominee, Potawatomi, Miami, Shawnee, Delaware, Cheyenne, Blackfeet, and Arapaho. Scholars have established this classification by language, but this does not mean the tribes were closely related or that they were allies. Mandan, Hidatsa, and Arikara Nation (Three Affiliated Tribes) 404 Frontage Road New Town, ND 58763 701-627-4781 www.mhanation.com Demographics Tribal enrollment 14,322 (Three Affiliated Enrollment Office 2015) Population (All Races) 6,341 (Census 2010) Population (Indian) 4,556 (Census 2010) Government The reservation was established under the Fort Laramie Treaty of 1851 and modified over the years, resulting in the final establishment of the reservation by the Executive Order of April 12,1870. Congressional acts and executive orders gradually reduced the reservation to its present size from the initial 12.5 million acres. In 1972, a federal court ruling determined that land lost to homesteaders through the 1910 Homestead Act had, in fact, always been part of the reservation. The constitution for the Three AfEliatedTribes was adopted on May 15, 1936. The tribal council is made up of seven members, including a chairman elected at-large by the tribal membership and one representative from each of the reservations six districts of Four Bears, Mandaree, Little Shell (New Town), Lucky Mound (Parshall), Twin Buttes, and White Shield. Council members serve four-year terms. Elections are held once every two years in November. The Fort Berthold Reservation spans approximately one million acres of both flat prairie land and rolling terrain in west-central North Dakota, southeast of Minot and northwest of Bismarck. The reservation is intersected by the Missouri River. About 11 percent of the total surface area is covered by Lake Sakakawea, the 440 2015-2017 North Dakota Blue Book